Sterilization Effects on Dimensional Accuracy of 3D-Printed Carbon Fiber-Reinforced Nylon (Transactions on Additive Manufacturing Meets Medicine, 2025)
Ensuring dimensional stability of additively manufactured (AM) medical components during sterilization is a critical yet understudied challenge. This study investigates the influence of geometry, continuous carbon fiber (CCF) reinforcement, and sterilization methods on the dimensional accuracy of fused filament fabricated (FFF) CCF reinforced nylon composites. 40 specimens of standard (ASTM D3039) and non-standard geometries were produced using Onyx®, both with and without CCF reinforcement. Printed samples were subjected to ethanol disinfection or steam autoclaving under ISO guidelines. MicroCT imaging was conducted before and after sterilization, and 3D geometric analysis was performed.Sterilization type did not affect surface deviation post treatment (p=0.1643), but deviations were primarily influenced by part geometry (p
Keywords: Additive Manufacturing; Continuous Fiber Reinforced Polymers; Dimensional Accuracy; Quality Management Systems; Medical Devices